Numerical modelling of rainfall-induced internal erosion process within vegetated deposited slopes - Xiaoqin Lei; Weiyu Zhang; Siming He; Shishu Zhang; Zongji Yang; Changbing Qin; Xiaoqing Chen (Journal of Rock Mechanics and Geotechnical Engineering)
The hydro-mechanical responses of vegetated deposited slopes are complex and far from clear. On one hand, the soils in deposited slopes are typically poorly consolidated and widely graded, making them vulnerable to internal erosion during rainfall infiltration. On the other hand, vegetation plays a significant role in influencing the hydro-mechanical properties of the soil at the slope surface. This paper presents a coupled seepage-erosion model to investigate the rainfall-induced internal erosion process within vegetated deposited slopes and its impact on slope stability. The detailed seepage-erosion coupling processes were simulated for a series of 1D rooted soil columns with varying root distributions, as well as 2D vegetated layered slopes under both light and heavy rainfall conditions. The numerical results reveal that roots can significantly mitigate rainfall-induced internal erosion, even with shallow root lengths. However, their protective effect on the slope increases as the root density in the superficial soil layer increases. Transpiration can rapidly restore matric suction in the shallow soil during rain intervals, slowing the rainfall-induced seepage-erosion process and thereby increasing slope stability. However, in the absence of transpiration, roots may either accelerate or inhibit the seepage-erosion process, depending on the specific rainfall conditions.